2021
DOI: 10.1182/bloodadvances.2021004976
|View full text |Cite
|
Sign up to set email alerts
|

Benign and malignant hematologic manifestations in patients with VEXAS syndrome due to somatic mutations in UBA1

Abstract: Somatic mutations in UBA1 involving hematopoietic stem and myeloid cells have been reported in patients with the newly defined VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, somatic) syndrome. Here, we report clinical hematologic manifestations and unique bone marrow (BM) features in 16 patients with VEXAS. All patients were male and had a history of severe autoinflammatory and rheumatologic manifestations and a somatic UBA1 mutation (p.Met41). Ten patients had hematologic disorders: myelodysplastic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
176
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 164 publications
(196 citation statements)
references
References 47 publications
11
176
0
9
Order By: Relevance
“…Beck et al [1] reported the presence of lupus anticoagulant (LA) in 12 (48%) of 25 patients with VEXAS syndrome. Obiorah et al [4] also reported that 7 (44%) of 16 patients had persistently positive LA and 5 (55.5%) out of 9 patients with VTE had positive LA. One patient also had weakly positive IgM anticardiolipin antibodies.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Beck et al [1] reported the presence of lupus anticoagulant (LA) in 12 (48%) of 25 patients with VEXAS syndrome. Obiorah et al [4] also reported that 7 (44%) of 16 patients had persistently positive LA and 5 (55.5%) out of 9 patients with VTE had positive LA. One patient also had weakly positive IgM anticardiolipin antibodies.…”
Section: Discussionmentioning
confidence: 92%
“…The recently published and largest case series by Georgin-Lavialle et al [3] described the rate of unprovoked VTE at 35.3% (41 out of 116 patients). Obiorah et al [4] reported an even higher VTE rate at 56.25% (9 out of 16 patients), with 60% of thrombotic events occurring within the first 2 years of disease onset. 7 patients were observed to have recurrent VTE with a median of 2 events per patient, with 3 patients were noted to have recurrent VTEs despite being on therapeutic anticoagulation.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations